2005
DOI: 10.1177/0013164404273941
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Analysis with Unidimensional Binary Data

Abstract: The present simulation investigated the performance of parallel analysis for unidimensional binary data. Single-factor models with 8 and 20 indicators were examined, and sample size (50, 100, 200, 500, and 1,000), factor loading (.45, .70, and .90), response ratio on two categories (50/50, 60/40, 70/30, 80/20, and 90/10), and types of correlation coefficients (phi and tetrachoric correlations) were manipulated. The results indicated that parallel analysis performed well in identifying the number of factors. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
73
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 32 publications
(55 reference statements)
12
73
0
2
Order By: Relevance
“…The PA results were slightly superior to the OPA results, were nonetheless unsatisfactory. Similarly, Horn (1965) reported that the PA produced consistently determines the threshold values of important components (Beaducel, 2001;Franklin, Gibson, Robertson, Pohlmann, & Fralish, 1995;Weng & Cheng, 2005). This finding is also consistent with the parallel analysis results of data obtained from a 5-point Likert scale (Kalkan, 2014).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The PA results were slightly superior to the OPA results, were nonetheless unsatisfactory. Similarly, Horn (1965) reported that the PA produced consistently determines the threshold values of important components (Beaducel, 2001;Franklin, Gibson, Robertson, Pohlmann, & Fralish, 1995;Weng & Cheng, 2005). This finding is also consistent with the parallel analysis results of data obtained from a 5-point Likert scale (Kalkan, 2014).…”
Section: Discussionsupporting
confidence: 76%
“…Because sample size exerts the largest effect on RMSR, increasing the sample size increases the estimation accuracy (Hooper et al, 2008;Thomas, 2003). Weng and Cheng (2005) stated that tetrachoric correlations in small samples introduces errors in large samples. Eight sample sizes yielded good fits (RMSR < .05) when based on the Pearson correlation, decreasing to 5 when using tetrachoric correlation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Timmerman and Lorenzo-Seva (2011) demonstrated that when using the minimum rank factor analysis extraction method, polychoric correlations are preferred to Pearson correlations for parallel analysis when the item data are ordered categorical. Weng and Cheng (2005) found that a parallel analysis yielded quite accurate decisions regarding the number of factors retained for binary data, but their study considered only a one-factor model. Cho, Li, and Bandalos (2009) evaluated the accuracy of parallel analysis for ordinal item data.…”
mentioning
confidence: 99%
“…Clarification for findings in Green (1983), Collins et al (1986), and Roznowski et al (1991) was provided by Weng and Cheng (2005). Weng and Cheng varied the number of items, the factor loadings and difficulties of the items, and sample size.…”
Section: Assumptions Associated With the Classical Factor Modelsmentioning
confidence: 99%